Identification of the discrepancy bone-teeth in children between 5 and 11 years with oral breathing - Clotilde de la Caridad Mora Pérez; Raúl López Fernández; Ramón Ahmed Pérez García; Amaray Calzada Bandomo; Ileana Pérez Rodríguez; María de los Santos Haces Yanes (Medisur)
Background: The correct proportion between teeth arches and size is crucial, thus there are different methods to measure dental size. Objective: To apply the method Moyer-Jenkin and its modification in mixed dentition. Method: Analytical, cross-sectional design, developed in the period January-April, 2007. The sample included 60 children between the ages of 5 and 11 years with oral breathing and Angle Class II and mixed dentition from the primary school "Guerrillero Heroico", Health Area II in Cienfuegos. Microsoft Word and SPSS 15.0 in English were used to process data. The studied variables were: measures and time. Results: The measurements of bone-teeth discrepancies for both maxillas were similar for both methods, without statistical significant differences. Regarding the discrepancy level, there was a moderated discrepancy in the studied group, with a marked increase in the mandible. There was a prevalence of normal incisive index and a reduction of macrodontism in negative discrepancies. Conclusions: The effectiveness of the modified method was proved, related with the reduction of the application time compared with Moyers-Jenkin method.